2012
DOI: 10.1002/jmv.23209
|View full text |Cite
|
Sign up to set email alerts
|

Discordance in HIV‐1 Co‐receptor use prediction by different genotypic algorithms and phenotype assay: Intermediate profile in relation to concordant predictions

Abstract: Concordant and discordant genotypic predictions of HIV-1 co-receptor tropism were analyzed. V3 region was sequenced from plasma samples of patients screened for R5 tropism by the Trofile® assay, before CCR5 antagonist prescription. Ten tools including geno2pheno, PSSM, an "11/25" and "net charge" rule, and other published algorithms were used. Patients were grouped according to concordance or discordance between tools and Trofile® result. Trofile® tropism reports from 50 patient samples were R5 in 38 and Dual/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
3
11
0
1
Order By: Relevance
“…A multitude of studies have compared the efficacies of phenotypic and genotypic assays to detect and quantify HIV-1 drug resistance (116)(117)(118)(119)(120) or coreceptor tropism (38,(121)(122)(123)(124). While there is usually high concordance between drug resistance methodologies (13,119,120), in general, population-based sequencing HIV-1 tropism tests are less sensitive and less specific than phenotypic assays (8,41).…”
Section: Discussionmentioning
confidence: 99%
“…A multitude of studies have compared the efficacies of phenotypic and genotypic assays to detect and quantify HIV-1 drug resistance (116)(117)(118)(119)(120) or coreceptor tropism (38,(121)(122)(123)(124). While there is usually high concordance between drug resistance methodologies (13,119,120), in general, population-based sequencing HIV-1 tropism tests are less sensitive and less specific than phenotypic assays (8,41).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared the efficacy of phenotypic and genotypic HIV-1 tropism assays to detect non-R5 variants (64)(65)(66)(67)(68). In general, population-based sequencing tests are less sensitive and less specific than phenotypic assays (14,29), although a few studies have shown significant concordance and similar predictive values (40,68,69).…”
Section: Discussionmentioning
confidence: 99%
“…Several currently available in silico co-receptor prediction methods have provided comparable results [232, 234, 253, 281, 285, 286]. However, one study was performed with co-receptor predictions based on 83 plasma samples from HIV-1 subtype B-infected individuals, utilizing three different in silico co-receptor prediction methods (wet-cat, PSSM, and geno2pheno) compared with a phenotypic assay [285].…”
Section: Pitfalls Of Co-receptor Usage Predictionmentioning
confidence: 99%